Pembentukan Lingkungan Religius Dalam Pengelolaan Pendidikan di SMP Negeri I Camplong - Ismail Ismail; Saniri Saniri; Abu Samsuddin; Moh. Taufiqurrahman (LP2M IAI Nazhatut Thullab Sampang, 2018)
Abstract The adjustment was implemented with the formation of a religious environment in the educational management at Camplong Junior High School 1. This research aims to get answers from the focus of the problem: 1) How is the formation of a religious environment in the educational management at Camplong Junior High School 1? 2) What are the supporting and inhibiting factors for the formation of a religious environment in the educational management at Camplong Junior High School 1? In order to collect data, researchers used interviewing, observation and documentation techniques. While the analysis is carried out according to descriptive analysis techniques quality. From the analysis of the data, it was found that: 1) the formation of a religious environment was realized by educational facilities and infrastructure that support, the existence of intra-religious and extra-curriculum religious activities, and religious attitudes and behavior of school people. 2) As for the supporting are teacher professionalism, educational facilities and infrastructure, and school discipline. The inhibiting factor is that the program is still centered on PAI teachers. Key Word: Religius Environment, Educational Management Abstrak Penyesuaian diimplementasikan dengan pembentukan lingkungan religius dalam pengelolaan pendidikan di SMP Negeri 1 Camplong. Penelitian ini bertujuan untuk mendapat jawaban dari fokus masalah: 1) Bagaimana pembentukan lingkungan religius dalam pengelolaan pendidikan di SMP Negeri 1 Camplong? 2) Apakah faktor pendukung dan penghambat pembentukan lingkungan religius? Dalam rangka pengumpulan data, peneliti menggunakan teknik wawancara, observasi dan dokumentasi. Sedangkan analisisnya dilakukan menurut teknik analisis deskriptif kualitatitf. Dari analisis data, ditemukan bahwa: 1) pembentukan lingkungan religius diwujudkan dengan: sarana dan parasana pendidikan yang mendukung, adanya kegiatan keagamaan baik intra maupun ekstra kurikulum, dan sikap dan perilaku religius warga sekolah. 2) adapun faktor pendukung yaitu profesionalisme guru, sarana dan prasarana pendidikan, dan tata tertib sekolah. Faktor penghambat adalah program ini masih terpusat pada guru PAI. Kata kunci: Lingkungan religius, pengelolaan pendidikan.